The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1021/ja909143d
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Perturbation of the Trinuclear Copper Cluster in the Multicopper Oxidases: The Role of Active Site Asymmetry in Its Reduction of O2 to H2O

Abstract: The multicopper oxidase Fet3p catalyzes the four-electron reduction of dioxygen to water, coupled to the one-electron oxidation of four equivalents of substrate. To carry out this process the enzyme utilizes four Cu atoms: a type 1, a type 2, and a coupled binuclear, type 3 site. Substrates are oxidized at the T1 Cu, which rapidly transfers electrons, 13 Å away, to a trinuclear copper cluster composed of the T2 and T3 sites where dioxygen is reduced to water in two sequential 2e − steps. This study focuses on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
99
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(108 citation statements)
references
References 54 publications
7
99
2
Order By: Relevance
“…1a; Augustine et al, 2010 Lee, George et al, 2002;Palmer et al, 2002;. It has previously been demonstrated that protons are not involved in all steps of the reduction of O 2 at the TNC (Augustine et al, 2007) ) is symmetrically located between the binuclear T3Cu-T3 0 Cu cluster (Augustine et al, 2010). Thus, after the two two-electron transfers have taken place, the NI displays four catalytic Cu ions in the cupric state and forms the RS by releasing one H 2 O molecule ( Fig.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…1a; Augustine et al, 2010 Lee, George et al, 2002;Palmer et al, 2002;. It has previously been demonstrated that protons are not involved in all steps of the reduction of O 2 at the TNC (Augustine et al, 2007) ) is symmetrically located between the binuclear T3Cu-T3 0 Cu cluster (Augustine et al, 2010). Thus, after the two two-electron transfers have taken place, the NI displays four catalytic Cu ions in the cupric state and forms the RS by releasing one H 2 O molecule ( Fig.…”
Section: Introductionmentioning
confidence: 94%
“…1) starting from the fully Cu reduced (FR) enzyme with four catalytic Cu ions in the cuprous state ( Fig. 1a; Augustine et al, 2010 Lee, George et al, 2002;Palmer et al, 2002;. It has previously been demonstrated that protons are not involved in all steps of the reduction of O 2 at the TNC (Augustine et al, 2007) ) is symmetrically located between the binuclear T3Cu-T3 0 Cu cluster (Augustine et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations